INFLUENCE OF COMMUNITY EDUCATION ON PARTICIPATION OF CITIZENS IN ENVIRONMENTAL SANITATION ACTIVITIES IN ANAMBRA STATE, NIGERIA - Okafor, Scholastica Ngozi (Journal of Continuing and Development Education, 2022)
The focus of this study was to ascertain the influence of community education on participation of the citizens in environmental sanitation activities in Anambra State of Nigeria. One research question and one hypothesis guided the study. The study adopted a descriptive survey design. Stratified random sampling technique was used and a sample of 1,543 was taken from 15,421 male and female adult learners who participated in Adult Education and Non-formal Education in Anambra State. The validation of the instrument was done by the experts in the fields of education and a reliability coefficient of 0.78 was procured using Gonbach’s Alpha. Mean and standard deviation were used to analyse data for the research questions while t-test was used to test the null hypothesis at 0.05 level of significance. The study revealed that people’s participation in community education programme enhanced citizens’ involvement in environmental sanitation activities in Anambra State. There was no significant difference in the mean ratings of male and female adult learners on the influence of community education on the citizens’ participation in environmental sanitation in Anambra State. It was recommended that the adult and Non-formal Education should be established in all the communities in Anambra State to enhance the citizens’ participation in community education programmes